Short-Term N2 Fixation Kinetics in a Moss-Associated Cyanobacteria - Jean, Marie-Eve; Cassar, Nicolas; Setzer, Cameron; Bellenger, Jean-Philippe (Environmental science & technology, 2012)
N2 fixation by moss-associated cyanobacteria plays an important role in the nitrogen cycling of terrestrial ecosystems. Recent studies have mainly focused on boreal ecosystems; little is known about such association in other ecosystems. Moss-associated cyanobacteria are subject to rapid changes (hourly or less) in environmental conditions that may affect N2 fixation kinetics. Using a recently developed method (Acetylene Reduction Assays by Cavity ring-down laser Absorption Spectroscopy, ARACAS) with higher sensitivity and sampling frequency than the conventional method, we characterize short-term kinetics of N2 fixation by cyanobacteria on moss carpets from warm and cold temperate forests. We report the identification of a heretofore unknown multispecies true-moss–cyanobacteria diazotrophic association. We demonstrate that short-term change in abiotic variables greatly influences N2 fixation. We also show that difference in relative proportion of two epiphytic diazotrophs is consistent with divergent influences of temperature on their N2 fixation kinetics. Further research is needed to determine whether this difference is consistent with a latitudinal trend.